A Partial Race to the Bottom : Corporate Tax Developments in Emerging and Developing Economies - Park, Junhyung; Abbas, S. M. Ali.; Bedi, Sukhmani; Klemm, Alexander (Washington, D.C. : International Monetary Fund, 2012)
This paper assembles a new dataset on corporate income tax regimes in 50 emerging and developing economies over 1996-2007 and analyzes their impact on corporate tax revenues and domestic and foreign investment. It computes effective tax rates to take account of complicated special regimes, such as partial tax holidays, temporarily reduced rates and increased investment allowances. There is evidence of a partial race to the bottom: countries have been under pressure to lower tax rates in order to lure and boost investment. In the case of standard tax systems (i.e. tax rules applying under normal circumstances), the effective tax rate reductions have not been larger than those witnessed in advanced economies, and revenues have held up well over the sample period. However, a race to the bottom is evident among special regimes, most notably in the case of Africa, creating effectively a parallel tax system where rates have fallen to almost zero. Regression analysis reveals higher tax rates adversely affect domestic investment and FDI, but do raise revenues in the short-run.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet